2018
DOI: 10.1101/471201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Fermented Idesia Polycarpa Residues supplementation on laying performance of Laying Quails

Abstract: L. Tang). Tel: (028) 8541 7281 Abbreviated Title:A new feeding raw material applying on laying quails.ABSTRACT: Idesia polycarpa Maxim. var. vestita Diels (Idesia polycarpa), which is 1 widely distributed in south China, is still underexplored. This study applied Idesia 2 polycarpa defatted fruit (IPF) and Candida utilis to the feed of laying quails using 3 solid-state fermentation. In comparison to the standard diet group, birds fed with 4 mixture of IPF and candida utilis (MIC) showed better production capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Idesia polycarpa is not only an excellent resource for developing new wood-based edible oils but also has good development value in many fields. The fresh fruit of Idesia polycarpa can be used as raw material to make edible sauces (Li, 2018). Cellular experiments have shown that Idesia polycarpa defatted extract can improve non-alcoholic fatty liver disease by activating antioxidant signaling pathways and regulating lipid metabolism (Li et al, 2020), and it was confirmed that it can delay or prevent skeletal muscle atrophy by inhibiting apoptosis (Jung et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Idesia polycarpa is not only an excellent resource for developing new wood-based edible oils but also has good development value in many fields. The fresh fruit of Idesia polycarpa can be used as raw material to make edible sauces (Li, 2018). Cellular experiments have shown that Idesia polycarpa defatted extract can improve non-alcoholic fatty liver disease by activating antioxidant signaling pathways and regulating lipid metabolism (Li et al, 2020), and it was confirmed that it can delay or prevent skeletal muscle atrophy by inhibiting apoptosis (Jung et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Many studies (Kim et al, 2005;Yang, 2008;Jung et al, 2010;Lee et al, 2013;Li, 2018;Li et al, 2020;Song, 2021;Chen et al, 2022;Wen et al, 2022;Xiang et al, 2023) reported the chemical and functional analyses of Idesia polycarpa fruit, but there is limited research on wild samples collected from different geographical regions. Furthermore, the antioxidant property analysis and correlation between all components still require attention.…”
Section: Introductionmentioning
confidence: 99%